Intensification of Potential Coconut Product Production in Kebun Kelapa Villages in order to Improve Welfare - Annisa Ilmi Faried; Maya Syaula; Geby Citra Ananda (International Journal of Management, Economic and Accounting, 2023)
To solve the issue of coconut derivative product diversification and differentiation, which necessitates rapid adoption of technology and industrial innovations to boost the selling price of coconuts in Kebun Kelapa Village, the relationship between farmers and industry is still inefficient, preventing the formation of synergies that can streamline the market with cooperation. Motivating this study is the belief that cultivating coconuts can significantly boost local economies, especially in Kebun Kelapa Village, which has a great deal of coconut potential but faces challenges in its connectivity to other economic centers. Results from hypothesis testing show that both prospective variables and natural resources have a considerable impact on output. Then, the potential variable has a substantial impact on coconut farmers' revenue, whereas the variables of access to finance and the quality of technology have little impact on farmers' output and earnings. According to the results of this analysis, both farmers and the government need to work toward the same goal of increasing the revenue of coconut growers.